2018
DOI: 10.1371/journal.pone.0203336
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality in pain medicine: A randomized experiment of pain perception, heart rate and religious spiritual well-being by using a single session meditation methodology

Abstract: The aim of this study is to investigate different effects on pain perception among randomly assigned volunteers practicing meditation compared to a relaxation condition. The study examines whether participants of the experimental conditions (meditation versus relaxation) differ in the change of pain perception and heart rate measurement and in religious and spiritual well-being after an intervention. Method: 147 volunteers (long-term practitioners and novices) were randomly assigned to the experimental conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 71 publications
2
20
0
1
Order By: Relevance
“…Based on the limited findings of previous research, it can be assumed that the RSWB dimensions can be changed in principle. However, these dimensions may need to be specifically addressed by means of a uniquely developed treatment protocol (e.g., Sollgruber et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the limited findings of previous research, it can be assumed that the RSWB dimensions can be changed in principle. However, these dimensions may need to be specifically addressed by means of a uniquely developed treatment protocol (e.g., Sollgruber et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…26 Studies have demonstrated reduced feelings of pain, fatigue, and anxiety in people with R/S practices. [27][28][29] Research has highlighted the crucial role of religious coping in men and women with cancer. However, little is known about the gender differences in religious coping with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the validity test with Pearson Product-Moment on the independent variables showed that there were three invalid questions, namely numbers 1,5 and 8 with validity levels moderate to very high (0.50 -0.90). The dependent variable test results showed 9 numbers namely items 5,10,12,13,16,17,18,19,20 issued, the rest are used for instruments with the validity moderate to high (0.40 -0.80). The reliability test by Cronbach's Alpha of Pain Management Strategy as the dependent variable showed the result as 0.874 (good) and 0.964 (excellent) for the independent variable (spiritual health condition).…”
Section: A Resultsmentioning
confidence: 99%
“…Also, giving birth is an experience of spiritual transformation [19]. Spirituality does not work with the intensity of the pain, but it could increase the ability to tolerate the pain [20]. So, the ability to manage the pain requires knowledge, techniques and practice to be trained.…”
Section: Independent Variablementioning
confidence: 99%